The extracellular matrix protects Pseudomonas aeruginosa biofilms by limiting the penetration of tobramycin. (10th June 2013) - Tseng, Boo Shan; Zhang, Wei; Harrison, Joe J.; Quach, Tam P.; Song, Jisun Lee; Penterman, Jon; Singh, Pradeep K.; Chopp, David L.; Packman, Aaron I.; Parsek, Matthew R.
Summary Biofilm cells are less susceptible to antimicrobials than their planktonic counterparts. While this phenomenon is multifactorial, the ability of the matrix to reduce antibiotic penetration into the biofilm is thought to be of limited importance studies suggest that antibiotics move fairly rapidly through biofilms. In this study, we monitored the transport of two clinically relevant antibiotics, tobramycin and ciprofloxacin, into non‐mucoid Pseudomonas aeruginosa biofilms. To our surprise, we found that the positively charged antibiotic tobramycin is sequestered to the biofilm periphery, while the neutral antibiotic ciprofloxacin readily penetrated. We provide evidence that tobramycin in the biofilm periphery both stimulated a localized stress response and killed bacteria in these regions but not in the underlying biofilm. Although it is unclear which matrix component binds tobramycin, its penetration was increased by the addition of cations in a dose‐dependent manner, which led to increased biofilm death. These data suggest that ionic interactions of tobramycin with the biofilm matrix limit its penetration. We propose that tobramycin sequestration at the biofilm periphery is an important mechanism in protecting metabolically active cells that lie just below the zone of sequestration.